THE COUNTER-NARRATIVE AND THE DECONSTRUCTION OF COLONIAL DISCOURSE: REPRESENTATIONS OF RESISTANCE IN ABDELRAZAK BOUKEBBA’S FAST-INFLAMING BLOOD - Yasmina Aouadi; Naim Garelmetred (International Journal of Innovative Technologies in Social Science, 2025)
This study analyzes Algerian writer Abdelrazak Boukebba’s short story collection Fast-Inflaming Blood as a subtle counter-narrative that subverts and deconstructs colonial narrative, particularly in its representations of the Palestinian cause. Drawing on the Edward Said’s theoretical model and broader currents within postcolonial thought—namely, the notion of "counter-narrative"—the article examines the way the book transforms structural violence in the form of siege, bombardment, and forced migration into a literary process that reframes the notions of embodiment, space, and temporality. Through advanced aesthetic and intellectual strategies, Boukebba’s book rewrites the colonial period as a dynamic arena of cultural resistance rather than as a passive victimization narrative and cultural recovery. The methodological approach employed combines critical cultural analysis with interpretive literary inquiry, allowing for a nuanced reading of how memory, identity, and resistance are configured within the text. Particular attention is given to stories such as Special Courage, in which the burial of a child becomes a ritual of resilience, and A Special Sea, where the fragmentation of space under occupation is rearticulated as a collective archive of memory. Everyday symbols—like an olive unearthed from a rocket crater or a sea narrated through oral tradition—serve not merely as metaphors but as acts of cultural survival. Ultimately, the study contends that Fast-Inflaming Blood stands as a paradigmatic example of literature’s power to dismantle colonial paradigms and to reimagine resistance as an enduring, embodied, and spatially grounded force.